Accessibility of Low-cost Insulin From Illegitimate Internet Pharmacies: Cross-sectional Study - Benjamin Penley; Lana Minshew; Hui-Han Chen; Stephen Eckel; Sachiko Ozawa (JMIR Publications, 2022)
BackgroundThere is much public debate regarding the high cost of insulin. With 1-in-4 patients in the United States with type 1 diabetes reporting difficulties affording insulin, there is concern that some of these patients might look for cost savings on the internet, unaware that 96% of internet pharmacies are illegitimate. Patients who purchase insulin from illegitimate internet pharmacies remove themselves from traditional health care systems that ensure safe, quality-assured, and effective medication use. ObjectiveThis study aims to determine the accessibility of Humalog and NovoLog insulin from internet pharmacies and characterize how these sites approached patient safety, and priced as well as marketed their products. MethodsFrom September to December 2019, we queried the phrases buy insulin online, buy Humalog online, and buy NovoLog online in common search engines. The first 100 search results from Google and Bing, and the first 50 search results from Yahoo! and DuckDuckGo were screened. Websites were included if they claimed to sell Humalog or NovoLog insulin, were active, free access, in the English language, and had a unique URL. The legitimacy of websites was classified using LegitScript. Safety and marketing characteristics were compared across the legitimacy of internet pharmacies. Internet pharmacy prices were compared with the prices offered through brick-and-mortar pharmacies using GoodRx. ResultsWe found that 59% (n=29) of the 49 internet pharmacies in our analysis were illegitimate, whereas only 14% (n=7) were legitimate and 27% (n=13) were unclassified. Across illegitimate internet pharmacies, Humalog and NovoLog insulin were 2 to 5 times cheaper as compared with both legitimate internet pharmacies and brick-and-mortar stores. Risks associated with the use of illegitimate internet pharmacies by American consumers were evident: 57% (8/14) did not require a prescription, 43% (6/14) did not display medication information or warnings, and only 21% (3/14) offered access to purported pharmacists. This included 9 rogue internet pharmacies that sold Humalog and NovoLog insulin within the United States, where 11% (1/9) required a prescription, 11% (1/9) placed quantity limits per purchase, and none offered pharmacist services. Rogue internet pharmacies often offered bulk discounts (11/18, 61%), assured privacy (14/18, 78%), and promoted other products alongside insulin (13/18, 72%). The marketing language of illegitimate internet pharmacies appealed more to quality, safety, and customer service as compared with legitimate sites. ConclusionsThe ease of access to low-cost insulin through illegitimate internet pharmacies calls for urgent attention. Illegitimate internet pharmacies place patients at risk of poor-quality medications and subpar pharmacy services, resulting in adverse events and poor diabetes control. A multifaceted approach is needed to close illegitimate internet pharmacies through legal and regulatory measures, develop better search engine filters, raise public awareness of the dangers of illegitimate internet pharmacies, and address the high costs of insulin.